Sensorless direct power control for three-phase grid side converter integrated into wind turbine system under disturbed grid voltages - Boukhechem, Ismail; Boukadoum, Ahcen; Boukelkoul, Lahcene; Lebied, Rima (Національний технічний університет "Харківський політехнічний інститут", 2020)
Wind turbines with permanent magnet synchronous generator (PMSG) are widely used as sources of energy connected to a grid. The studied system is composed of a wind turbine based on PMSG, a bridge rectifier, a boost converter, and a controlled inverter to eliminate low-order harmonics in grid currents under disturbances of grid voltage. Traditionally, the grid side converter is controlled by using the control VFOC (Virtual Flux Oriented Control), which decouple the three-phase currents indirect components (id) and in quadratic (iq) and regulate them separately. However, the VFOC approach is dependent on the parameters of the system. This paper illustrates a new scheme for the grid-connected converter controller. Voltage imbalance and harmonic contents in the three-phase voltage system cause current distortions. Hence, the synchronization with the network is an important feature of controlling the voltage converter. Thus, a robust control method is necessary to maintain the adequate injection of the power during faults and/or a highly distorted grid voltage. The proposed new control strategy is to use the direct power control based virtual flux to eliminate side effects induced by mains disturbances. This control technique lowers remarkably the fluctuations of the active and reactive power and the harmonic distortion rate. The estimated powers used in the proposed control approach is calculated directly by the positive, negative, and harmonic items of the estimated flux and the measured current without line sensor voltage.

Ветряные турбины с синхронным генератором на постоянных магнитах (PMSG) широко используются в качестве источников энергии, подключенных к сети. Исследуемая система состоит из ветряной турбины на основе PMSG, мостового выпрямителя, повышающего преобразователя и управляемого инвертора для устранения гармоник низкого порядка в токах сетки при возмущениях напряжения сети. Традиционно преобразователь на стороне сети управляется с помощью виртуального потокоориентированного управления VFOC (Virtual Flux Oriented Control), который разделяет трехфазные токи на косвенные компоненты (id) и на квадратичные компоненты (iq) и регулирует их отдельно. Однако подход VFOC зависит от параметров системы. Данная статья иллюстрирует новую схему для контроллера преобразователя, подключенного к сети. Дисбаланс напряжения и содержание гармоник в трехфазной системе напряжения вызывают искажения тока. Следовательно, синхронизация с сетью является важной особенностью управления преобразователем напряжения. Таким образом, надежный метод управления необходим для поддержания адекватной подачи энергии во время неисправностей и/или значительно искаженного напряжения сети. Предложенная новая стратегия управления заключается в использовании виртуального потока на основе прямого управления мощностью для устранения побочных эффектов, вызванных помехами в сети. Этот метод управления значительно снижает колебания активной и реактивной мощности и уровень гармонических искажений. Оценочные мощности, используемые в предлагаемом подходе к управлению, рассчитываются непосредственно по положительным, отрицательным и гармоническим элементам оцененного потока и измеренного тока без напряжения линейного датчика.
Keywords: permanent magnet synchronous generator; синхронный генератор с постоянными магнитами